(untitled) (Studia Prawnicze / The Legal Studies, 1984)
The problems of the separation of church and state and freedom of religion are most often discussed in American constitutionalism. The author’s goal is to study thoroughly the US version of separation ecclesiae et status and point to its unique features. Thus, the most important problem is the interpretation of the clause of an establishment of religion in the First Amendment to the Constitution, expressing the principle of separation, by the federal Supreme Court and constitutionalists. After having analyzed the principle of equality, voluntarism, non-interference of the state in religious matters, accomodation of the state, cooperation of the church and state, neutrality of the state, the author comes to the conclusion that the separation of church and state in the USA has been determined by the principle of neutrality, consisting in neutral policy of the state in the field of religious matters. He also considers the relation between the principle of freedom of conscience and worship and the institution of separation saying that, excluding exceptional situations, in case of a conflict the principle of freedom of worship should be of a primary importance. He does not agree that both clauses on religion of the First Amendment (there is also a clause on free exercise of religion) constitute a new principle. In order to find out what form of neutrality the policy on religion has assumed in the American Union, the author refers to the ideology and public life, considering the attitude of federal and state authorities towards religion. He finds out that the state does not prefer any particular religion or religious unions but supports religion in general as a social phenomenon. The author creates a theoretical model of the separation consisting of the following rules: I. Organizational separatness of state and church machineries; II. Fulfillment of the principle of freedom of conscience and worship; III. Lay- character of the state resulting from the policy of neutrality towards religion; IV. The same attitude of the state towards denominations as to associations. In the USA all features of this model have been implemented, with exception Of rule III which has been implemented only partially. Summing up, a characteristic feature of the American version of the separation of church and state is traditional policy of friendly neutrality towards denominatoins (church) combined with the support for religion as a form of social consciousness.